Clinical evaluation of the DermaGenius® Nail real-time PCR assay for the detection of dermatophytes and Candida albicans in nails. (11th May 2018) - Hayette, Marie-Pierre; Seidel, Laurence; Adjetey, Caroline; Darfouf, Rajae; Wéry, Marie; Boreux, Raphaël; Sacheli, Rosalie; Melin, Pierrette; Arrese, Jorge
Abstract: Onychomycosis represents one of the most frequent mycoses in the world. Causative agents are mainly dermatophytes, but yeasts and nondermatophyte moulds can also be involved. Conventional diagnostic methods include direct microscopy (or histology) and culturing. However, molecular methods are becoming increasingly popular in this field. The DermaGenius ® (DG) Nail multiplex assay (PathoNostics, The Netherlands) is a new commercial real-time polymerase chain reaction (PCR) kit, which can detect Trichophyton rubrum, Trichophyton interdigitale and Candida albicans directly in nails. The present study is a retrospective evaluation of the kit applied to 138 finger and toenail clippings in comparison to histology and culture methods. The sensitivity and specificity of the PCR assay are 80% (76/95) and 74.4% (32/43), respectively, when histology and culture are used as reference to define onychomycosis. DG performance is not different from histology combined with culture ( P = .11) but the best diagnostic efficacy (88.4%, 122/138) is obtained by the combination of histology and DG. In conclusion, this study emphasizes the clinical usefulness of the DG in diagnostics. The high specificity of this test guarantees a better identification compared to culture that can lead to dermatophyte misidentifications. It is a reliable PCR assay that shortens the time to diagnosis and can unmask the presence of nongrowing fungal pathogens in nails.